StAR-Related Lipid Transfer (START) Domains Across the Rice Pangenome Reveal How Ontogeny Recapitulated Selection Pressures During Rice Domestication - Mahtha, Sanjeet Kumar; Purama, Ravi Kiran; Yadav, Gitanjali (Frontiers in Genetics, 2021)
START proteins, encoded by a plant amplified family of evolutionary conserved genes, play important roles in lipid binding, transport, signaling, and modulation of transcriptional activity in the plant kingdom, but there is limited information on their evolution, duplication and associated sub- or neo-functionalization. Here we perform a comprehensive investigation of this family across the rice pangenome, using ten wild and cultivated varieties. Conservation of START domains across all ten rice genomes suggests low dispensability and critical functional roles for this family, further supported by chromosomal mapping, duplication and domain structure patterns. Analysis of synteny highlights a preponderance of segmental and dispersed duplication among STARTs, while transcriptomic investigation of the main cultivated variety Oryza sativa var. japonica reveals sub-functionalization amongst genes family members in terms of preferential expression across various developmental stages and anatomical parts, such as flowering. Ka/Ks ratios confirmed strong negative/purifying selection on START family evolution, implying that ontogeny recapitulated selection pressures during rice domestication. Our findings provide evidence for high conservation of START genes across rice varieties in numbers, as well as in their stringent regulation of Ka/Ks ratio, and showed strong functional dependency of plants on START proteins for their growth and reproductive development. We believe that our findings advance the limited knowledge about plant START domain diversity and evolution, and pave the way for more detailed assessment of individual structural classes of START proteins among plants and their domain specific substrate preferences, to complement existing studies in animals and yeast.